Assessment of Chemical and Electronic Surface Properties of the Cu2ZnSn(SSe)4 After Different Etching Procedures by Synchrotron-based Spectroscopies. (December 2015) - Olar, Tetiana; Lauermann, Iver; Xie, Haibing; Neuschitzer, Markus; Saucedo, Edgardo; Calvet, Wolfram; Steigert, Alexander; Ümsür, Bünyamin; Chacko, Binoy; Parvan, Vladimir; Gorgoi, Mihaela; Senkovskiy, Boris; et al.
Abstract: Kesterite Cu2 ZnSn(S, Se)4 absorber layers with different [S]/([S]+[Se]) ratios were studied using XPS, UPS, Hard X-ray (HIKE) photoemission and the Near Edge X-ray Absorption Fine Structure spectroscopy (NEXAFS). The samples were prepared by IREC using sequentially sputtered metallic precursor stacks with metal ratios of [Cu]/([Zn]+[Sn])=0.80, [Zn]/[Sn]=1.20 followed by annealing under S+Se+Sn atmosphere. Different etching procedures were used depending on the sample's composition. It is shown that the surface composition varies from that of the bulk, especially for the Se-rich samples. Contamination with sulfur is detected after using a Na2 S etching solution for the pure Se kesterite. A Cu-depleted surface was found for all samples before and after etching. HIKE measurements show a higher [Zn]/[Sn] ratio in the near surface region than on the very surface. This is explained by the fact, the etching procedure removes secondary phases from the very few surface layers, while some of ZnS(e) is still buried underneath. In order to investigate the band gap transition from the pure sulfide (1.5 eV) to the pure selenide (1eV), the valence and conduction band of the respective absorbers were probed. According to UPS and HIKE measurements, the relative distance between Fermi level (Ef ) and valance band maximum (VBM) for sulfide sample was 130 meV larger than for selenide. Using NEXAFS on the copper, zinc and tin edges, the development of the conduction band with increasing [S]/([S]+[Se]) ratios was studied. Stoichiometric powder samples were used as reference materials.